Human T-lymphotropic virus type 1(HTLV-1) associated infective dermatitis - Hlela, C (2011)
Human T lymphotropic virus type -1 (HTLV-1) infections are important causes of mortality and morbidity in endemic areas worldwide. There is neither a vaccine specific for the virus nor satisfactory treatment for the associated malignancy or inflammatory syndromes. HTLV-1 associated infective dermatitis (IDH) is a chronic dermatitis that has been observed in a variable proportion of HTLV-1 infected children. IDH may serve as an early clinical marker for HTLV-1 and an indicator of increased risk for developing other HTLV-1 associated conditions such as adult T cell leukaemia/lymphoma (ATLL) and HTLV-1-associated myelopathy or transient spastic paraparesis (HAM/TSP). However the mechanisms underlying IDH and the relationships with HAM/TSP and ATLL are poorly understood. We undertook skin biopsies from 14 cases with IDH, and controls which included five asymptomatic carriers (ACs) and 18 healthy uninfected individuals from South Africa. We conducted clinical assessments, proviral load, allergen-specific IgE, peripheral blood and cutaneous T cell and virological analyses. We obtained relevant clinical history and examined all cases and controls based on a pre-formed questionnaire. Despite the partial clinical similarities with atopic dermatitis, the individuals with IDH did not have an increased incidence of atopic disease including asthma or rhinitis. Furthermore house dust mite-specific IgE levels were not elevated in the cases compared to the controls, suggesting that atopy is not a predisposing factor for the development of IDH in HTLV-1 infected individuals. Circulating proviral load was significantly higher in those with IDH compared to asymptomatic carriers and skin biopsy revealed acanthosis, and lymphocytic epidermotropism associated with a superficial perivascular and periadnexal lymphocytic infiltration of CD8+, and CD4+ T cells. Furthermore IDH associated with an infiltrate of epidermal and dermal FoxP3+ T cells and lesional down-regulation of filaggrin expression compared to non-lesional skin. We did not observe an elevation of pro-inflammatory cytokines in the sera of individuals with IDH compared to the controls. We investigated integration patterns in the skin and blood of 10 cases with IDH, and two asymptomatic carrier (AC) individuals from South Africa. We first showed that the virus is present in the skin at high levels (total mean levels of 47.09 proviral copies per 1000 cells) as comparable to that which has been observed in blood (total mean levels 137 proviral copies per 1000 cells). Using a high throughput Illumina sequencing system in collaboration with Professor Bangham, we mapped and quantified the relationship between oligoclonal proliferation of HTLV-1 infected T cells in the skin and blood of IDH patients. It was found that in IDH, a selective outgrowth of certain clones is favoured, supporting the possibility of skin-specific factors exerting positive selection on proliferation. In IDH, there was not a preferential integration of the provirus in transcriptionally active regions of the gene sites, as had been observed in other HTLV-1 associated conditions. These observations imply that the selection forces that favour oligoclonal proliferation of HTLV-1+ T cells differ fundamentally between simple HTLV-1 infection and other events associated with the dermatitis. In conclusion, these data show that HTLV-1 is not associated with an atopic diathesis. Given the lack of elevated pro-inflammatory cytokines and presence of a cutaneous infiltrate of FoxP3+ T cells, the findings suggest that high levels of HTLV-1 replication promotes a regulatory environment leading to filaggrin down-regulation, cutaneous susceptibility to infection, and secondary inflammatory skin disease. Viral integration patterns would support the presence of skin-specific positive selection, perhaps eventually leading to expansion of particular clones with the potential to develop towards ATLL. It remains to be explained whether the high viral load in IDH changes over time, more specifically in the steps leading to ATLL.